2013
DOI: 10.1007/s10096-013-1837-5
|View full text |Cite
|
Sign up to set email alerts
|

International dissemination of Escherichia coli strains with discrepant behaviour in phenotypic antimicrobial susceptibility tests

Abstract: Preventing the dissemination of antimicrobial resistance depends on appropriate antibiotic stewardship and accurate antimicrobial susceptibility testing (AST). We report the international dissemination of Escherichia coli strains, showing discrepancies between reference methods when phenotypically tested for susceptibility to piperacillin/tazobactam (TZP). We demonstrate that these related strains are predisposed to problematic TZP AST interpretations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Previous work revealed that E. coli clinical isolate 907355 is resistant to piperacillin-tazobactam (TZP; MIC for the combination, >128 µg/ml piperacillin and 4 µg/ml tazobactam [expressed here as ≥128/4 µg/ml]) in BMD tests, yet susceptible (MIC, ≤16/4 µg/ml) by the AD method ( 24 , 25 ). To further investigate the nature of this discordant behavior, BMD assays were performed with two other β-lactam/β-lactamase inhibitor combinations, ampicillin-sulbactam (SAM) and amoxicillin-clavulanate (AMC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work revealed that E. coli clinical isolate 907355 is resistant to piperacillin-tazobactam (TZP; MIC for the combination, >128 µg/ml piperacillin and 4 µg/ml tazobactam [expressed here as ≥128/4 µg/ml]) in BMD tests, yet susceptible (MIC, ≤16/4 µg/ml) by the AD method ( 24 , 25 ). To further investigate the nature of this discordant behavior, BMD assays were performed with two other β-lactam/β-lactamase inhibitor combinations, ampicillin-sulbactam (SAM) and amoxicillin-clavulanate (AMC).…”
Section: Resultsmentioning
confidence: 99%
“…We have identified a number of clinical E. coli isolates that exhibit discordant behavior and heterogeneous resistance in disk diffusion (DD), agar dilution (AD), and broth microdilution (BMD) antibiotic susceptibility testing (AST) assays ( 24 , 25 ). A PCR- and sequence-based screen for plasmid-borne β-lactamase genes revealed that many of the isolates harbored only bla TEM-1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, certain drugs (especially combinations) are often problematic. Root causes for such differences are usually unknown, but clear differences between piperacillin-tazobactam (TZP) broth microdilution (BMD) and agar dilution (AD) results were observed for isolates of several species (2)(3)(4)(5). Although differences between BMD and AD have been observed for other species, the population analysis discussed here was limited to Escherichia coli.…”
mentioning
confidence: 99%
“…Although differences between BMD and AD have been observed for other species, the population analysis discussed here was limited to Escherichia coli. We recently demonstrated that this aberrant phenotype can be clonal in E. coli (5). In this study, isolates were tested by population analysis (PA) in order to determine whether heterogeneity of resistance expression was a factor in the category differences observed between BMD and AD for TZP.…”
mentioning
confidence: 99%
See 1 more Smart Citation